Helminths parasites of digestive trackt of sheep and goats in Macedonian region
During two periods (December 1985-October 1986 and October 1990-April 1991), the digestive tracts of 102 sheep and 29 goats were examined, with the purpose to find out and identify the helminthes parasites of these animals. The 96,1% of sheep and 93,1% of goats were found to be infected with 26 and 20 different helminths, respectively. The nematodes which were found out of the different parts of the digestive tract of these animals were: Sheep: oesophagus: Gongylonema pulchrum, abomasum: Haemonchus contortus, Teladorsagia circumcincta, T. trifurcata, Trichostrongylus axei and Cooperia oncophora, small intestine: Teladorsagia circumcincta, Trichostrongylus colubriformis